Experimenting the Effect of Process Writing on EFL Students - Magfirah Yuniar; irwand irwandi; Muhammad Hudri (Linguistics and ELT Journal, 2019)
The purpose of this study was to find out the effect of process writing as an alternative strategy on teaching English writing in an EFL classroom. The process involved pre-writing, drafting, revising, editing, and publishing. 28 out of senior high school students participated in this quasi-experimental research. The experimental group was taught using process writing, while the control one without any process that was by writing the product approach. The data were then collected through writing tests about recount texts before and after the treatment and were analyzed using SPSS. The results showed there was a significant difference between students’ scores. The students who were taught using process writing had higher scores on average than students’ who were taught without using process writing. This result implied the strategy is effective for teaching writing for EFL students.